ANALISIS KUALITAS SUMBER DAYA MANUSIA DAN TINGKAT KEMISKINAN DI KABUPATEN OGAN KOMERING ILIR - Abukosim Abukosim; M Syirod Saleh; Taufiq Marwa (Jurnal Ekonomi Pembangunan, 2010)
This study aims to determine the relationship between the quality of human resources (education and health) with poverty rates at OKI. The data used are secondary data obtained from relevant agencies. The results of this study indicate that jointly variable quality of human resources (education and health) significantly affect the level of poverty. Partially variables that significantly affect the level of poverty is education level, the higher the education level of the lower poverty levels. Health variables (the ratio of health facilities and health workers) did not significantly affect the level of poverty. Keywords: Human Resources, Poverty